Research Productivity in the Health Sciences in Saudi Arabia: 2008-2017 - Ikram Ul Haq; Shafiq Ur Rehman; Hanan M. Al-Kadri; Rai Khalid Farooq (Annals of Saudi Medicine, 2020)
The purpose of this study was to analyze the published research on health sciences carried out by researchers in Saudi Arabia in the last decade by assessing bibliometric output. Data for 2008 to 2017 was retrieved from Scopus. During this period, there was significant growth, from 1332 publications in 2008 to 5529 in 2017, with an average annual growth rate of 14.1%. King Saud University was the most productive institution. Most of the published research was done in collaboration with Egypt. The subject area of medicine was predominant with the main publication source being the Saudi Medical Journal, Life Science Journal, the Acta Zhengzhou University Oversea Version, and the Annals of Saudi Medicine, primarily in the form of original research articles. The growing trend in publications is a sign of the increasing quality of education and more research and development activities, which are made possible by a sufficient budget allocation to these activities during the last decade.